Assessment of the FINDRISC tool in predicting the risk of developing type 2 diabetes mellitus in a young adult Nigerian population - Nnamudi, Anthony Chibuzor (2023)
Data on 134 young adults [67 (50.0%) male and 67 (50.0%) female] analyzed in this study revealed a body mass index value of 24.86 ± 3.38 kg/m2 (male) and 25.42 ± 5.39 kg/m2 (female) with 43.2% of participants being overweight or obese. A waist circumference of 85.94 ± 9.69 cm (male) and 83.92 ± 15.24 cm (female) was recorded with 35.8% of participants having central obesity. A fasting blood glucose level of 82.04 ± 14.52 mg/dL (male) and 84.89 ± 18.30 mg/dL (female) was recorded with 32.8% of participants being hyperglycemic. The Finnish Diabetes Risk Scoring (FINDRISC) data [4.86 ± 3.24 (male) and 7.31 ± 3.38 (female)] showed that 1.5% have a high risk (FINDRISC 15–20) while 12.0% have a moderate to high risk (FINDRISC ≥ 12) of developing diabetes.